PERGUMULAN PEMIKIRAN PENDIDIKAN ISLAM DENGAN THEOLOGI, PERIPATISME, GNOSISME, ILUMANISME, DAN TRANSDENTALISME - Ika Hairani (UIN Sumatera Utara Medan, 2018)
Abstact: This paper describes the school of thought in education. The schools are theology, Peripatismism, Gnosticism, Ilumanism and Transdentalism. The thought of Islamic education has evolved from the classical era until now. It cannot be denied that in the course of science scientists face various phases and events from the point of view of Religion, Social, Culture and politics. In Religion, many Qur'anic verses that explain about this education, thus the verses that are in the Qur'an are interpreted differently according to the historical background of the scientist who interpreted the verse. Socially, educational thinking is influenced by different scientific backgrounds. Culturally, educational thinking is influenced by scientists whose cultural lives vary. There are those who live in Eastern culture, Western culture, and some live in classical and modern times, all of which affect the flow of thought. Politically, education thinking is also very influential. There are scientists who are born and raised in the environment of leadership disputes, in contrast to scientists who are born and raised in a period of calm of power. But in the end the thought of Islamic education is useful for the advancement of Islamic education itself, which leads Muslims and Muslim women to be happy in the world and akhrirat.